Heat transfer flow of Cu-water and Al2O3-water micropolar nanofluids about a solid sphere in the presence of natural convection using Keller-box method - Mohammed Z. Swalmeh; Hamzeh T. Alkasasbeh; Abid Hussanan; Mustafa Mamat (Results in Physics, 2018)
Natural convection boundary layer flow over a solid sphere in micropolar nanofluid with prescribed wall temperature is studied. Copper (Cu) and alumina (Al2O3) in water-based micropolar nanofluid has been considered. Tiwari and Das’s nanofluid model with realistic empirical correlations are considered to analyze the nanoparticles effects on natural convective flow. The nonlinear partial differential equations of the boundary layer are first transformed into a non-dimensional form and then solved numerically using an implicit finite difference scheme known as Keller-box method. The effects of nanoparticles volume fraction, Prandtl number, micro-rotation parameter on temperature, velocity and angular velocity are plotted and discussed. Further, numerical results for the local Nusselt number and the local skin friction coefficient are obtained. It is found that Cu has a low heat transfer rate as compare to Al2O3 water-based micropolar nanofluid with increasing micro-rotation parameter. The present results of local Nusselt number and the local skin friction for viscous fluid are found to be in good agreement with the literature. Keywords: Micropolar nanofluid, Natural convection, Solid sphere, Keller-box method